The principle of modularity as a design method in environmental design - Filatova Elena V. (Архитектон)
The article is a theoretical study on issues related to navigation design. A review of the historical stages in the emergence and development of visual communication systems abroad and in Russia is carried out. Research has shown that the ability to navigate in space forms a kind of visual and informational language of visual communications – as a system of various information carriers. The basic principles and rules for the design of visual navigation in multifunctional buildings have been developed, following which will make it possible to competently organize navigation systems. The article examines the design trends of a correct visual navigation system based on the analysis of the experience of visual interaction between the consumer and navigation systems. The theme of navigation design and orientation of people in space is a current trend in modern design. It is actively studied and developed based on the needs of representatives of the target audiences around the world.